Polly Ericksen on healthy people, resilient systems - Ericksen, Polly J. (International Food Policy Research Institute, 2014)
Polly Ericksen, Program Leader, ILRI, at the side event, "Healthy People, Resilient Systems." IFPRI 2020 conference on Building Resilience for Food and Nutrition Security, May 15-17, 2014, Addis Ababa, Ethiopia. More information at http://www.2020resilience.ifpri.info